Hubungan Asupan Makan, Dan Pola Asuh Ibu Dengan Kejadian Stunting Pada Balita - Diah Karlina (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Background: Stunting occurs when a child's height is lower than the average for their age due to poor growth caused by chronic malnutrition, which occurs when a child's nutritional intake is insufficient for an extended period. Stunting may have both direct and indirect causes. Direct causes include inadequate nutrition, while indirect causes include parenting practices. Food consumption is a behavior that improves the nutritional state of the body in a measurable way. Objective: This study aims to determine the relationship between food intake and maternal parenting practices with the occurrence of stunting in toddlers at Puskesmas Pancur Batu, Desa Tanjung Anom, Kecamatan Pancur Batu, Kabupaten Deli Serdang in 2024. Method: A quantitative, observational, cross-sectional technique was used in this study. The study will be conducted from June to July 2024. Primary and secondary data were used in this study. Data were analyzed using chi-square tests for bivariate and univariate analysis. Results: The findings show a significant correlation (p-value = 0.000 < 0.05) between food consumption and the occurrence of stunting. A p-value of 0.002 < 0.05 indicates a relationship between maternal parenting practices and the occurrence of stunting. Conclusion: There is a strong correlation between calorie consumption and stunting. Parental involvement is significantly related to the stunting rate. Recommendation: It is hoped that posyandu cadres and Puskesmas officials in the study area will receive greater appreciation for the role that parents play in monitoring the nutritional needs of their toddlers.